Kinerja Tim Serbu Api Kelurahan (TSAK) Dalam Penanggulangan Kebakaran Hutan Dan Lahan Di Kecamatan Sabangau Kota Palangka Raya: Performance Of Fire Assault Team Village (TSAK) In Overcoming Forest Fire And Land In Sabangau Subdistrict Of Palangka Raya City - Ratmoko, Ambar; Arbaini, Arbaini (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2018)
This research aims to determine the performance of the Village Fire Assault Team (TSAK) in response to forest fires and land in Sabangau sub-district Palangka Raya. The methods used are qualitative descriptive, primary and secondary data sources, observational data collection techniques, literature studies, and interviews. Performance of Fire Assault Team Village (TSAK) in Sabangau Sub-district of Palangka Raya is still not maximally described by seven indicators as follows, objectives: in the implementation of the task is still not reached as expected. Standard: Fire Assault Team (TSAK) still does not have SOP so it is difficult to know the success of a job. Feedback: The absence of feedback is difficult to perform performance improvements. Tool/means: still insufficient. Competence: already has knowledge and Kehlian in carrying out the task. Motive: No compensation in the promised both in terms of material and nonmaterial. Opportunity: There has been no hope because TSAK was formed not as a profession but the real purpose is social and humanitarian. The advice that can be conveyed to the establishment of disaster and fire Fighting Agency (BPBPK) Palangka Raya City among others: is expected to form/establish standard operational procedure (SOP), add/renew adequate equipment, Set a decent/standard wage, as well as finding a solution/policy on the future of TSAK members.